Icing on the cake or gilding the lily? The impact of high-modified model images on purchase intention. (September 2022) - Lv, Xingyang; Liang, Yuqing; Luo, Jia; Liu, Yue
Abstract: Marketers had high expectations for modified model images in E-commerce, however, the social movements against photoshopped models suggested the high-modified model images may be harmful to consumers which leads to a contradictory phenomenon. So far, the link between high-modified model image and consumers' behavior is not clearly understood. Drawing on a selective accessibility model (SAM), this study investigates the influence of high-modified model images on consumers' purchase intention by introducing the concept of misrepresentation and identifying consumer trust as a mediator. Based on five experiments, we demonstrate that over-modified model images decrease consumers' perceived authenticity referring to "misrepresentation", and further lower their purchase intention. By comparing the level of misrepresentation, the results suggest that high-modified model images decrease purchase intention. Moreover, this negative relationship between misrepresentation of modified model images and purchase intention is mediated by consumer trust. Hence, this study makes a step toward explaining how high-modified model images impacts the behaviors of consumers, shedding new light on the application of image modification in online advertising.